The environmental effects of air pollution from the energy sector in South Africa - Gerson, R (Energy Research Centre, 2016)
The literature and data describing the environmental effects of air pollution in South Africa were examined, with a focus on the effects that are produced by the use of energy. This examination consisted of three parts: The emissions resulting from the use of the different fuels were calculated, with a complete sectorial and regional breakdown for pollution sources. A review of the data obtained from pollution monitoring programmes conducted in South Africa was completed. It was found that while monitoring is conducted in various regions and urban districts, there are areas with recognised pollution problems, such as townships, where little or no monitoring has been conducted. Often the resulfs of monitoring programmes were not published, or only available in unprocessed form. The literature describing environmental effects related to air pollution was reviewed. The number of studies pertaining to South African environments was found to be limited and tended to focus on certain areas, while neglecting others. Areas requiring further study and research were identified.